Attitudes of Young Adult Consumers Regarding Food Safety During Meals Preparation - Eugenia CZERNYSZEWICZ; Magdalena NIEWCZAS-DOBROWOLSKA (Communications of International Proceedings, 2022)
A significant proportion of foodborne illnesses can be attributed to practices used in the processing of food in the household. Hence, recognizing the knowledge, opinions and practices of consumers is important from the point of view of preventing hazards to food safety. The aim of this research was to assess the knowledge, beliefs and behavior of young adult consumers in relation to food safety during the preparation of meals in their home. It is commonly believed that attitudes have a strong influence on consumer behavior. This research was carried out using the survey method. It turned out that positive beliefs and knowledge in the field of food safety are not adequately reflected in the reported behavior of respondents during the processing and preparation of meals. In addition, it was found that the attitudes of young adult consumers are most influenced by gender, as well as the place of purchase of food and decisiveness regarding food purchase.
Keywords: food safety; food; attitudes; preparing meals; ABC model